x − 4 5 x + 2 x × ( 0 . 2 ) x + 2 4 = 1 2 5 × ( 0 . 0 4 ) x − 4 x − 2
Solve for x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Alternatively, you can also proceed like this:
x + 2 1 = x − 4 x − 8 = ( x + 2 ) ( x − 2 ) x − 8 ⟹ x − 2 = x − 8 ⟹ x − x − 6 = 0 ⟹ ( x − 3 ) ( x + 2 ) = 0 ⟹ x = 3 ⟹ x = 9
The negative solution x = ( − 2 ) is rejected because it makes the original equation undefined.
Problem Loading...
Note Loading...
Set Loading...
( 5 x + 2 x × 5 − x + 2 4 ) x − 4 1 = 5 x + 2 1 = 5 3 + x − 4 2 ( 2 − x ) ⇒ x + 2 1 = x − 4 ( 3 x − 1 2 ) + 4 − 2 x = x − 4 x − 8 ⇒ x − 4 = ( x − 8 ) ( x + 2 ) Now let y = x , y 2 = x : ( y 2 − 8 ) ( y + 2 ) − y 2 − 4 = ( y 2 − 8 ) ( y + 2 ) − ( y + 2 ) ( y − 2 ) = ( y + 2 ) ( y 2 − y − 6 ) = ( y + 2 ) 2 ( y − 3 ) = 0 Now 0 1 is undefined so x = y = − 2 ⇒ x = 3 ∴ x = 9 .